ANALISIS DAN DESAIN ULANG TAMPILAN ANTARMUKA SISTEM INFORMASI MANAJEMEN PUSKESMAS DI PUSKESMAS DANUREJAN II YOGYAKARTA - , INNEKE UDAYANA K; , Nur Rokhman, S.Si., M.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As quoted from the book of âPetunjuk dan Pemanfaatan Data SP2TP - Ministry of Health of the Republic of Indonesiaâ, in the implementation of health development efforts community health center has obliged heatlh programs and development health programs. Recording and reporting in the context of Health Information Systems is a supporting activity of each of the programs. Along with the data and information needs of community health center, Ministry of Health of the Republic of Indonesia has made a policy through community health center management information system which is the main source is integrated recording and reporting system community health center. The implementation of management information system in Danurejan II community health center not include activities of integrated recording and reporting system, this problem make the availability of data and information that is accurate, affordable and timely as an essential condition management of envidence-based decision making to support efforts to achieve the objectives of national health systems do not work. The purpose of this research is to analyze and redesign the user interface of information management system Danurejan II community health center whic is accordance with the requirements. The result of this research is final design of the user interface management information system community health center according to user demand and existing report formats.